2016
DOI: 10.1590/s0080-623420160000100014
|View full text |Cite
|
Sign up to set email alerts
|

Cost of nursing turnover in a Teaching Hospital

Abstract: OBJECTIVE To map the sub processes related to turnover of nursing staff and to investigate and measure the nursing turnover cost. METHOD This is a descriptive-exploratory study, classified as case study, conducted in a teaching hospital in the southeastern, Brazil, in the period from May to November 2013. The population was composed by the nursing staff, using Nursing Turnover Cost Calculation Methodology. RESULTS The total cost of turnover was R$314.605,62, and ranged from R$2.221,42 to R$3.073,23 per emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 12 publications
0
33
0
4
Order By: Relevance
“…The abandonment of work affects the productivity of employees and the quality of nursing care (Mirarchi Vieira & Kurcgant, 2010;Tironi, deSilva, Dellaroza, do Haddad, & Vannuchi, 2014) and creates institutional expenses associated with the recruitment and training of replacement employees (Hogh, Hoel, & Carneiro, 2011). A Brazilian study reported that the cost of nursing staff turnover represented three times the average salary of the nursing team (Ruiz, Perroca, & Jericó, 2016). In Brazil, turnover has been used as an important indicator of the quality of hospital management (PROAHSA, 2018).…”
mentioning
confidence: 99%
“…The abandonment of work affects the productivity of employees and the quality of nursing care (Mirarchi Vieira & Kurcgant, 2010;Tironi, deSilva, Dellaroza, do Haddad, & Vannuchi, 2014) and creates institutional expenses associated with the recruitment and training of replacement employees (Hogh, Hoel, & Carneiro, 2011). A Brazilian study reported that the cost of nursing staff turnover represented three times the average salary of the nursing team (Ruiz, Perroca, & Jericó, 2016). In Brazil, turnover has been used as an important indicator of the quality of hospital management (PROAHSA, 2018).…”
mentioning
confidence: 99%
“…A study on turnover costs among a teaching hospital nursing team showed that the financial impact of lost employees was three times the mean nursing wage, indicating the need for improving personnel policies aimed at nurse retention (17) .…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to underline the high organizational costs related to staff management processes resulting from the turnover (training of people, recruitment, and selection for personnel renewal; Halter et al, 2017). The cost of turnover involves the pre-hiring (notice, recruitment, vacancies, and hiring) and post--hiring processes (guidance, training, reduced productivity of new employees, cancellations, and rescissions; Ruiz, Perroca, & Jericó, 2016). A case study conducted in Brazil aimed to map the sub-processes related to the nursing team turnover and measure their costs (Ruiz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%